Impact of Combined Osmotic Stress and Prosopis Juliflora Induced Allelopathy on Germination and Recovery of Selected Crops in Tunisia - Rahmani, Rami; Aydi, Samir; Aydi, Sameh Sassi; Debouba, Mohamed (Global Journal Of Botanical Science, 2022)
Few studies has been conducted on interaction between P. juliflora leaf extract sand crop germination under water deficit in arid regions. We conducted laboratory trials in order to evaluate crop species germination and recovery potentials under the combined effects of osmotic stress (0.4, 0.8 and 1 MPa) and allelopathic action of P. juliflora leaf extracts (0, 2.5%, 5% and 10%). Four crop species were assessed: Wheat (Triticum durum), barley (Hordeum vulgare), lettuce (Lactuca sativa) and tomato (Solanum lycopersicum). Statistical analyses highlighted a selective negative action of allelopathy on monocots compared to dicots. Combination of osmotic and allelopathic stresses exacerbated the negative effects on seed germination of all four species. Osmotic stress was the dominant factor, whereas allelopathy was the secondary factor when the two stresses were combined. While all treatments reduced germination, even at low stress levels, partial and total recovery levels were reported. Tomato, the least stress tolerant species, showed the highest recovery. In short, leaf extracts of P. juliflora exacerbated the effect of osmotic stress on seed germination of barley and wheat. In addition, the crops displayed differential adaptive strategies when exposed to the combined stresses.